Literasi Edukasi Pola Hidup Sehat Dan Bersih Terhadap Anak Pekerja Migran di Malaysia - Marisa Trisofirin; Hadi Cahyono; Ardhana Januar Mahardhani; Shohenuddin Shohenuddin (Educativo: Jurnal Pendidikan, 2023)
Migrant children often experience difficulties in accessing information and proper health facilities. Information literacy is a great way to educate migrant children. Therefore, this community service research aims to educate the children of migrant workers about a healthy and clean lifestyle. The method used in this education is a participatory method, with the participation of guidance studio students who take part in Healthy Thursday and Clean Thursday activities. The results of this activity have a positive impact, especially on awareness of the importance of maintaining health by doing gymnastics and keeping the environment clean. This can be seen from the joy of the children and their enthusiasm in participating in this education..